Examen especial al área de crédito y su incidencia en la rentabilidad de la Empresa Comercial Dávila, cantón La Maná, provincia de Cotopaxi, periodo 2020 - Arauz Zamora, Karla Katherine (2022)
The special examination establishes the verification, study, and evaluation of limited aspects or of a part of the activities related to the financial, administrative, and operational activity of an entity with the objective of verifying the correct use of the available resources and the fulfillment of regulations or rules apply in the context. The aim of the research is to apply a special examination to the credit area and determine its impact on the profitability of the “Comercial Dávila” company, through quantitative, field, bibliographic, descriptive, and applied research using methods: deductive, inductive, and analytical. For the collection of data, the respective interview was carried out with the owner-manager, and the survey was applied to the officials involved in the established control area. Each of the phases involved in the special examination was planned with their respective supporting documents, allowing it to be deduced that the internal control system of “Comercial Dávila" identifies certain deficiencies in compliance with the Internal Control Standards and legal provisions established for the correct development of the economic activity of private companies, thus minimizing the development of each of the scheduled activities within the annual accounting year. As a possible solution to the problem encountered, it is recommended as an alternative solution to implement the proposal for an easy and simple Manual of Policies and Procedures to be applied with a view to improving the management of collections on credit and the recovery of overdue portfolio issued by the company “Comercial Dávila”.